Вплив музичного мистецтва на психіку людини - Монакова, В. О. (ХНУРЕ, 2025)
This thesis explores the influence of music on the emotional state of individuals, incorporating historical and contemporary examples. It examines the role of music in cultural and ritual practices, its ability to affect emotions, cognitive functions, and physiology. Particular attention is given to the analysis of scientific studies and the practical application of music in therapy, education, and the creation of comfortable environments. Music serves as a universal means of communication and emotional impact, contributing to the harmonization of relationships and the enhancement of quality of life.
Keywords: музичне мистецтво; психіка людини